Unveiling the Power of STEAM: An Innovative Look at Early Childhood Education in the Caribbean Region of Colombia - Castañeda Robles, Harold
This article explores the integration of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in the Early Childhood Education programs of the Colombian Institute of Family Welfare (ICBF) in the Caribbean region of Colombia. The author seeks to analyze the challenges and opportunities that such integration represents, in order to enrich pedagogical strategies and promote quality comprehensive development for the children served. From a phenomenological perspective, the study adopts a qualitative methodology, collecting data through semi-structured interviews and observations of 100 educational agents participating in a STEAM training diploma course. The results reveal that, although there are challenges such as the need for teacher training and didactic resources, the implementation of STEAM has a positive impact on the development of key skills in children. The author concludes that ICBF has the opportunity to assume a transformative leadership role by adopting an organizational culture centered on educational excellence through the comprehensive integration of STEAM. Future lines of research include further exploration of teacher training strategies, acquisition of resources, and family and community participation.